Распространение гипотезы о переходных процессах в электроцепях на полигармонические входные воздействия - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
The hypothesis about the transient processes in electric circuits with polyharmonic input voltages is developed. The electric current in an RL circuit is calculated.